(untitled) (Current Horticulture, 2024)
The experiment was conducted to find out the effect of foliar spraying of micronutrient on growth and yield of potato (Solanum tuberosum L.) during 2019-20 at Vegetable Research Farm, Department of Horticulture, BHU, Varanasi. The experiment was laid out in a randomised block design with 3 replications having 9 treatments. The treatments were T1 ( control), T2 (B-20 (boron) @ 0.06%), T3(B-20 (boron) @ 0.09%), T4(zinc sulphate @ 0.03%), T5 (zinc sulphate @ 0.05%), T6 (B-20 (boron) @ 0.06% + zinc sulphate @ 0.03%) T7 (B-20 (boron) @ 0.06% + zinc sulphate @ 0.05%), T8 (B-20 (boron) @ 0.09% + zinc sulphate @ 0.03%) and T9 (B-20 (boron) @ 0.09% + zinc sulphate @ 0.05%). T9 (B-20 (boron) @ 0.09% + zinc sulphate @ 0.05%) was found to be the best for all the growth and yield traits except for number of leaves in that T3 (B-20 (boron) @ 0.09%) was recorded with highest value, for the rest trait followed by T7 (B-20 (boron) @ 0.06% + zinc sulphate @ 0.05%) and T8 (B-20 (boron) @ 0.09% + zinc sulphate @ 0.03%), while the least value was observed in T1 (control) that was sprayed with water.